Traditional dietary assessment tools verses technology-based methods in children and adolescence. An updated review: Traditional and technological diet assessment methods - Baghlaf, Khlood (Progress in Nutrition, 2022)
Dietary assessment in children is challenging for several reasons. In research, there are several challenges in the accurate assessment of diet and nutrition. In particular, the selection of the most appropriate dietary assessment method for their study. The aim of this review is to summarize the most common traditional and technology-based tools that are used in children for dietary assessment implementation. Traditional diet assessment methods are available to assess children dietary intake in research, each one with different strengths and weaknesses. The most common dietary measures to assess children’s diet are food frequency questionnaires, weighed food records, 24 hour recall and diet history interviews because they are valid accurate measures Recently, several technology-based tools have been introduced to provide a more accurate record of portion size using visualisations and to improve the participation response of traditional dietary surveys. These new measurement tools optimized to use on mobile phones and tablets, which makes it more accessible for participants. The development of technology-based dietary measures now allows for a detailed analysis of the whole diet on different days and at different times of the day with low-cost, precision and convenient to patients.